Pleural abrasion should not routinely preferred in treatment of primary spontaneous pneumothorax - Zhang, Zhenrong; Du, Lanfang; Feng, Hongxiang; Liang, Chaoyang; Liu, Deruo (Journal of Thoracic Disease, 2017)
Background: The aim of this study was to find out whether thoracoscopic bullectomy with pleural abrasion (BLPA) could lower the recurrence ratio in primary spontaneous pneumothorax (PSP) patients compared with bullectomy alone. Methods: All PSP patients who underwent video assisted thoracoscopy (VATS) bullectomy (120 bullectomy cases) or BLPA (225 BLPA cases) in our department between 2008.1 and 2013.12 were retrospectively reviewed. Clinical data, perioperative data, and follow-up information were collected. Propensity score analysis was used in balancing preoperative factors between groups. Results: Three hundred and forty five patients (283 men and 62 women) with an average age of 27 (27.32±11.41) years old underwent 120 bullectomy and 225 BLPA in this study. There was no mortality or significant complication in both groups. More postoperative drainage (1,170.66±904.02 vs. 528.38±491.49, P